Radiographic measurements of the hind limbs in capuchin monkeys (Sapajus spp.) - de Souza Siragusi, Rafael H. [UNESP] (2023)
Background: Radiographic measurements are a useful tool to assess skeletal health and development in primates. This study aimed to perform radiographic measurements of hind limbs in capuchin monkeys. Methods: Twelve Sapajus spp. were used; ten adults and two sub-adults, nine females and three males. Results and conclusions: The pelvimetry showed that the pelvic inlet area presented mean values of 7.63, 10.23, and 5.43 cm2 for adult males, adult females, and sub-adult females, respectively. The mean inclination angle was 129.45° and the mean values for the mechanical lateral proximal and distal femoral angles were 102.32° and 90.93°, respectively. The mean values for the anatomic lateral proximal and distal femoral angles were 104.59° and 85.98°, respectively. In conclusion, the radiographic measurements proved feasible for hind limb evaluation in Sapajus spp. and can be used for comparison with animals presenting orthopedic lesions.